Changing times? Gender roles and relationships in maternal, newborn and child health in Malawi - Lucinda Manda-Taylor; Daniel Mwale; Tamara Phiri; Aisling Walsh; Anne Matthews; Ruairi Brugha; Victor Mwapasa; Elaine Byrne (BMC, 2017)
Abstract Background For years, Malawi remained at the bottom of league tables on maternal, neonatal and child health. Although maternal mortality ratios have reduced and significant progress has been made in reducing neonatal morality, many challenges in achieving universal access to maternal, newborn and child health care still exist in Malawi. In Malawi, there is still minimal, though increasing, male involvement in ANC/PMTCT/MNCH services, but little understanding of why this is the case. The aim of this paper is to explore the role and involvement of men in MNCH services, as part of the broader understanding of those community system factors. Methods This paper draws on the qualitative data collected in two districts in Malawi to explore the role and involvement of men across the MNCH continuum of care, with a focus on understanding the community systems barriers and enablers to male involvement. A total of 85 IDIs and 20 FGDs were conducted from August 2014 to January 2015. Semi-structure interview guides were used to guide the discussion and a thematic analysis approach was used for data analysis. Results Policy changes and community and health care provider initiatives stimulated men to get involved in the health of their female partners and children. The informal bylaws, the health care provider strategies and NGO initiatives created an enabling environment to support ANC and delivery service utilisation in Malawi. However, traditional gender roles in the home and the male 'unfriendly' health facility environments still present challenges to male involvement. Conclusion Traditional notions of men as decision makers and socio-cultural views on maternal health present challenges to male involvement in MNCH programs. Health care provider initiatives need to be sensitive and mindful of gender roles and relations by, for example, creating gender inclusive programs and spaces that aim at reducing perceptions of barriers to male involvement in MNCH services so that programs and spaces that are aimed at involving men are designed to welcome men as full partners in the overall goals for improving maternal, neonatal and child health outcomes.